2012
DOI: 10.1021/jf3020766
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Grape Berries According to Diameter and Total Soluble Solids To Study the Effect of Light and Temperature on Methoxypyrazine, Glutathione, and Hydroxycinnamate Evolution during Ripening of Sauvignon blanc (Vitis vinifera L.)

Abstract: Grape berries were classified according to diameter and total soluble solids (TSS) to study the effect of light and temperature on methoxypyrazines (MPs), glutathione (GSH), and hydroxycinnamates (HCAs) during the ripening of Sauvignon blanc. The light exposure of the fruiting zone was modified within leaf and lateral removal at the phenological stage berry of peppercorn size and no removal (control). In comparison to the control, the concentration of 3-isobutyl-2-methoxypyrazine (IBMP) was below the limit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 43 publications
7
38
2
Order By: Relevance
“…Most of them have focused their research on the main aroma molecules: glycosylated aroma precursors, free aroma volatiles, C 13 ‐norisoprenoids, terpenes, and methoxypyrazines. Although the removal of basal leaves around a bunch is usually chosen to increase the exposure to light, some authors have used artificial shading (e.g., boxes) …”
Section: Agronomic Practicesmentioning
confidence: 99%
“…Most of them have focused their research on the main aroma molecules: glycosylated aroma precursors, free aroma volatiles, C 13 ‐norisoprenoids, terpenes, and methoxypyrazines. Although the removal of basal leaves around a bunch is usually chosen to increase the exposure to light, some authors have used artificial shading (e.g., boxes) …”
Section: Agronomic Practicesmentioning
confidence: 99%
“…γ-Glutamylcysteine synthetase produces γ-glutamylcysteine from L-glutamate and L-cysteine. Certain authors reported GSH concentrations in ripening grapes to increase up to about 16 degree Brix (Okuda and Yokotsuka, 1999), while others found levels to increase up to commercial harvest at around 25 degree Brix (Suklje et al, 2012). GSH can occur in white grapes at a few milligrams to more than 100 mg/kg (Kritzinger et al, 2013a), depending on the cultivar and ripening stage.…”
Section: Effects Of Production and Processingmentioning
confidence: 99%
“…However, their concentration decreases, especially in the skin, due to berry growth. HCA are synthesized in the early stages of berry formation, while levels decrease in the early stages of ripening, but then seem to stabilize at the later stages of ripening (Suklje et al, 2012). Flavonols have two distinct phases of synthesis: the first around flowering with the other during ripening of the grape berry (Downey et al 2003).…”
Section: Effects Of Production and Processingmentioning
confidence: 99%
“…Winemakers could thus harvest grapes at a lower grape sugar level to obtain a higher concentration of methoxypyrazines if greener notes are preferred or at a later stage if more tropical-associated aroma attributes are required in the wines (Pineau et al 2011). Factors such as growing Sauvignon Blanc grapes in cooler climates Swart 1999, Marais et al 1999) and less light exposure during ripening (Suklje et al 2012) can also increase IBMP concentration in Sauvignon Blanc wines and thus in greenassociated sensory attributes, such as green pepper and overall green. Skin contact before fermentation, which can further increase IBMP concentration (Maggu et al 2007), should also be considered if even a higher concentration is required with a potential increase in asparagus and green grass attributes.…”
Section: Aroma Attributes Reference Standard Compositionmentioning
confidence: 99%